2002
DOI: 10.1093/emboj/21.5.1112
|View full text |Cite
|
Sign up to set email alerts
|

Control of cytomegalovirus lytic gene expression by histone acetylation

Abstract: Permissiveness for human cytomegalovirus (HCMV) infection is dependent on the state of cellular differentiation and has been linked to repression of the viral major immediate early promoter (MIEP). We have used conditionally permissive cells to analyze differential regulation of the MIEP and possible mechanisms involved in latency. Our data suggest that histone deacetylases (HDACs) are involved in repression of the MIEP in non-permissive cells as inhibition of HDACs induces viral permissiveness and increases M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
266
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(288 citation statements)
references
References 76 publications
18
266
0
4
Order By: Relevance
“…Although HCMV virion contains no histone proteins [55,56], a number of reports indicate that host histones with different modifications associate with HCMV DNA in infected cells cultured in labs or isolated from humans [49,[57][58][59][60][61][62]. Nitzsche et al [43] further indicate that HCMV DNA is chromatinized in infected cells; histones are localized with UL44 at replication foci and there is a robust increase of histone occupancy coupled with viral DNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…Although HCMV virion contains no histone proteins [55,56], a number of reports indicate that host histones with different modifications associate with HCMV DNA in infected cells cultured in labs or isolated from humans [49,[57][58][59][60][61][62]. Nitzsche et al [43] further indicate that HCMV DNA is chromatinized in infected cells; histones are localized with UL44 at replication foci and there is a robust increase of histone occupancy coupled with viral DNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…Observations which show that YY1 can not only block the recruitment of the general transcription factor TFIIB to a pre-initiation complex on the MIEP, but can also recruit the chromatin re-modelling factor histone deacetylase 3 (HDAC3), offer at least two possible mechanisms for the specific repression of MIEP activity by this factor (Sinclair, 1999;Thomas & Seto, 1999). Indeed, we have recently shown that chromatin acetylation/deacetylation plays a major role in the control of the NIEP in permissive and non-permissive cells (Murphy et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Observations which show that YY1 can not only block the recruitment of the general transcription factor TFIIB to a pre-initiation complex on the MIEP, but can also recruit the chromatin re-modelling factor histone deacetylase 3 (HDAC3), offer at least two possible mechanisms for the specific repression of MIEP activity by this factor (Sinclair, 1999;Thomas & Seto, 1999). Indeed, we have recently shown that chromatin acetylation/deacetylation plays a major role in the control of the NIEP in permissive and non-permissive cells (Murphy et al, 2002).Our results reiterate that there is a degree of redundancy with respect to the sites through which a number of candidate repressors can prevent expression from the MIEP. Thus YY1 and ERF interact not only with the dyad repeat element, but also with the repeated 21 bp motif (Liu et al, 1994; Figs 2 and 4).…”
mentioning
confidence: 99%
“…93 Consequently, this might be used as an approach to render cytomegalovirus latently infected cells transiently visible to the host immune response ( Figure 6). In initial pilot experiments, we have been able to induce IE gene expression using histone deacetylase inhibitors in latently infected monocytes (Poole et al, unpubl.…”
Section: Induction Of Immunogenic Lytic Genes In the Absence Of Immunmentioning
confidence: 99%